2022
DOI: 10.1002/ajpa.24490
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomy of the ligaments and muscles of the radiocarpal joint in chimpanzees and humans

Abstract: Objectives In the present study, we have analyzed the anatomy of the radiocarpal joint ligaments and muscles in Pan troglodytes and Homo sapiens in order to identify similarities and differences between the two species that may be related to differences in hand use and function. Materials and Methods Anatomical dissections of the ligaments and muscles of the radiocarpal joint were performed in six adult chimpanzees and 12 humans. The mass of each ligament and of the functional ligament groups were calculated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Tuttle (1967) noted that severing of the palmar ligaments of the wrist significantly increased mobility in ulnar deviation in Pan troglodytes . Recent work (Potau et al, 2022) has shown that P. troglodytes has more heavily developed dorsal radiocarpal ligaments than Homo sapiens , while the reverse is true for the palmar radiocarpal ligaments. Potau et al (2022) suggest that the strong dorsal ligaments in Pan may relate to stabilizing the wrist in flexed hand positions during climbing, but these ligaments also appear to stabilize the hand in ulnar deviation as well (Tuttle, 1967).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuttle (1967) noted that severing of the palmar ligaments of the wrist significantly increased mobility in ulnar deviation in Pan troglodytes . Recent work (Potau et al, 2022) has shown that P. troglodytes has more heavily developed dorsal radiocarpal ligaments than Homo sapiens , while the reverse is true for the palmar radiocarpal ligaments. Potau et al (2022) suggest that the strong dorsal ligaments in Pan may relate to stabilizing the wrist in flexed hand positions during climbing, but these ligaments also appear to stabilize the hand in ulnar deviation as well (Tuttle, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work (Potau et al, 2022) has shown that P. troglodytes has more heavily developed dorsal radiocarpal ligaments than Homo sapiens , while the reverse is true for the palmar radiocarpal ligaments. Potau et al (2022) suggest that the strong dorsal ligaments in Pan may relate to stabilizing the wrist in flexed hand positions during climbing, but these ligaments also appear to stabilize the hand in ulnar deviation as well (Tuttle, 1967). The analysis of ligament function in a wider sample of primates using experimental or modeling techniques (e.g., Rainbow et al, 2012) along with quantitative assessment of the bony correlates of ligament attachment (e.g., Casado et al, 2019) would further elucidate form and function in the primate wrist.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies between Pan and hominins have provided a marked contribution to our understanding of hominin hand evolution. Such efforts have been diverse and in recent years include investigation of soft and hard tissue anatomy (e.g., Diogo et al, 2012; Dunmore et al, 2020; Karakostis et al, 2021; Potau et al, 2022; Stephens et al, 2016; Tocheri et al, 2008) and manual capabilities (e.g., Bardo et al, 2017; Domalain et al, 2017; Feix et al, 2015; Pouydebat et al, 2009), between Pan , Homo , and australopiths. However, the use of fossil hominins in these comparisons has, understandably, been limited to hard tissue investigations or modeling efforts.…”
Section: Introductionmentioning
confidence: 99%